How can the European Ecodesign Directive guide the deployment of hydrogen-related products for mobility?. Issue 6 (28th February 2023) - Campos-Carriedo, Felipe; Bargiacchi, Eleonora; Dufour, Javier; Iribarren, Diego
Abstract : Exploring (i) the practicality of the European ecodesign framework to address hydrogen-related products, and (ii) the relevance, under eco-efficiency and criticality aspects, of ecodesign measures aligned with projected key performance indicators. Abstract : Fuel cells and hydrogen products are expected to be increasingly deployed as European economies set course towards the energy transition. In order to actually contribute to the overall goal of sustainability, these products should be conceived as sustainable-by-design options and effective assessment tools are thus required to guide the design process. For the first time in the specific field of hydrogen-related products, this work tests and discusses the suitability of the instrument provided by the European Ecodesign Directive for such purposes: the EcoReport tool linked to the Methodology for Ecodesign of Energy-related Products. To that end, the propulsion systems of a fuel cell passenger car and a fuel cell heavy duty truck were assessed. First, two base cases defined according to current key performance indicators were implemented in the EcoReport tool to gain insights into ecodesign hotspots and gaps of the tool for its practical use to evaluate hydrogen-related products. Secondly, after adjusting the EcoReport tool according to the findings of the previous step, both cases were parametrised to estimate, under eco-efficiency and criticality aspects, up to which extent short-term technological targets could improve their performance. Overall, the EcoReport tool is concluded to be valuable for an early assessment and subsequent development of ecodesign measures for hydrogen-related products provided that it is upgraded in terms of direct data availability, updated criticality characterisation factors and impact assessment methods. By reaching the key performance indicators expected for 2030, the assessed products for mobility would arise as competitive road transport alternatives. Nevertheless, this performance is highly dependent on the production pathway of the hydrogen used as a fuel, which highlights the need for a holistic deployment of the hydrogen economy.